2018
DOI: 10.1038/s41598-017-18935-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ferroptosis and mitochondrial dysfunction by oxidative stress in PC12 cells

Abstract: Neurodegenerative diseases (NDD) are typically associated with neuron loss in nervous system areas. Interventions with related death mechanisms may ameliorate NDD progression. Oxidative stress plays an important role in NDD cell death routines. However, tert-butylhydroperoxide (t-BHP), a widely used oxidative stress stimulus, induces neural cell death through a mechanism that remains elusive. In our study, the ferroptosis marker events occurred after co-treatment with 100 μM t-BHP for 1 h, all of which were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 53 publications
5
103
0
Order By: Relevance
“…Recent studies have suggested that mitochondrial damage may be the final step of ferroptosis-related oxida-tive cell death in neurodegenerative diseases [156]. In a study of neurodegenerative diseases using PC12 cells, tert-butyl hydroperoxide (t-BHP) was reported to induce ferroptosis, which was accompanied by a decrease in mitochondrial membrane potential and ATP production as well as an increase in mitochondrial ROS [156].…”
Section: Relationship Between Ferroptosis and Mitochondria In Neurodementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that mitochondrial damage may be the final step of ferroptosis-related oxida-tive cell death in neurodegenerative diseases [156]. In a study of neurodegenerative diseases using PC12 cells, tert-butyl hydroperoxide (t-BHP) was reported to induce ferroptosis, which was accompanied by a decrease in mitochondrial membrane potential and ATP production as well as an increase in mitochondrial ROS [156].…”
Section: Relationship Between Ferroptosis and Mitochondria In Neurodementioning
confidence: 99%
“…Recent studies have suggested that mitochondrial damage may be the final step of ferroptosis-related oxida-tive cell death in neurodegenerative diseases [156]. In a study of neurodegenerative diseases using PC12 cells, tert-butyl hydroperoxide (t-BHP) was reported to induce ferroptosis, which was accompanied by a decrease in mitochondrial membrane potential and ATP production as well as an increase in mitochondrial ROS [156]. Previous studies have demonstrated that the separation of IRP-1 from IRE is ATP-dependent, so the depletion of ATP leads to enhanced IRP-1 and IRE binding activity, which in turn causes TFR upregulation and a subsequent increase in iron content [157].…”
Section: Relationship Between Ferroptosis and Mitochondria In Neurodementioning
confidence: 99%
“…Exogenous antioxidants have generated growing interest in preventing or reducing oxidative stress, in decreasing muscle soreness and physical stress, and in ameliorating sport performance [ 7 ]. The exogenous antioxidants act in addition to the endogenous ones, and the most known are tocopherols (vitamin E), ascorbic acid (vitamin C), carotenoids (β-carotene), ubiquinone and polyphenols [ 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that both apoptosis and ferroptosis are associated with ROS accumulation, we also examined whether loss of hTim8a increased vulnerability to this iron-dependent, lipid peroxidation-mediated form of regulated cell death (Dixon et al, 2012;Simon et al, 2000;Wu et al, 2018). Treatment with specific ferroptosis inducers, including: (i) Erastin, an SLC7A11 inhibitor; (ii) (1S,3R)-RSL3, which inhibits glutathione peroxidase 4 and (iii) buthionine sulfoximine (BSO), which depletes glutathione (GSH), did not enhance cell death of hTim8a MUT SH-SY5Y cells (Figure 6E).…”
Section: Loss Of Htim8a Sensitises Cells To Intrinsic Cell Deathmentioning
confidence: 99%